ANALYSIS OF LEVEL OF PREPAREDNESS COMMUNITY OF DISASTER EARTHQUAKE IN GANGGA SUB-DISTRICT - Apriyatno Apriyatno; Chatarina Muryani; Yasin Yusup; Nurhadi Nurhadi (Universitas Sebelas Maret (UNS), 2020)
Natural conditions and geographical situations in Indonesia show that natural disasters are very likely to occur. One of the natural disasters that occurred was an earthquake. The main factor in the occurrence of the earthquake which caused many losses was the lack of knowledge regarding the potential and community preparedness for the earthquake disaster. The purpose of this study was to determine the level of community preparedness in dealing with earthquake disasters. The method used is a qualitative method with sampling using a cluster random sampling of 75 respondents. Analysis of community preparedness uses scoring with the help of Geographic Information Systems on four parameters of preparedness, namely knowledge and attitudes, emergency response plans, disaster warning systems, and resource mobilization. The results of this study are Gangga District community preparedness is divided into two categories, namely the category of moderate preparedness and high preparedness. The category of preparedness is currently found in Bentek, Genggelang, and Rempek villages. Meanwhile, the category of high preparedness is found in Gondang village and Sambik Bangkol village. Considering that the Ganges District is an earthquake-prone area, it is expected that the government, family and community will be able to increase preparedness so that the community can live better in earthquake-prone areas.